1999
DOI: 10.1111/j.1745-4514.1999.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Embryogenesis in Anise (Pimpinella Anisum L.): The Effect of Proline on Embryogenic Callus Formation and Aba on Advanced Embryo Development

Abstract: Somatic embryos of anise (Pimpinella anisum) are an excellent system to investigate the biosynthesis of food‐related phenolic metabolites like anethol which is linked to differentiation. Somatic embryogenesis in anise is a two part system. The first is a 2,4‐D (2,4‐dichlorophenoxy acetic acid)‐induced embryogenic callus formation which requires optimal levels of endogenous auxin and cytokinin levels. The second is the advanced embryo development stage in the absence of 2,4‐D which requires abscisic acid to sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…L-proline was more prominent compared to two other amino acids (L-glutamine and L-serine) on SE maturation and plantlet formation. L-proline has been shown to possess a stimulatory effect during embryogenesis and to provide osmotolerance (Shimizu et al 1997;Bela and Shetty 1999;Hita et al 2003). In a previous study, L-proline was found to give optimum response of somatic embryogenesis in kodo millet when added with 2,4-D (Vikrant and Rashid 2002a); this was added in a single medium.…”
Section: Discussionmentioning
confidence: 96%
“…L-proline was more prominent compared to two other amino acids (L-glutamine and L-serine) on SE maturation and plantlet formation. L-proline has been shown to possess a stimulatory effect during embryogenesis and to provide osmotolerance (Shimizu et al 1997;Bela and Shetty 1999;Hita et al 2003). In a previous study, L-proline was found to give optimum response of somatic embryogenesis in kodo millet when added with 2,4-D (Vikrant and Rashid 2002a); this was added in a single medium.…”
Section: Discussionmentioning
confidence: 96%
“…Enrichment of the regeneration medium with amino acids and increased sucrose level may account for the differential response. The addition of amino acids to the culture medium has been shown to be beneficial to morphogenetic expression (Moghaddam et al 2000;Bela and Shetty 1999). With stem-derived callus of Tribulus terrestris, the addition of casein hydrolysate and yeast extract improved somatic embryogenesis of Tribulus terrestris callus cultures (Mohan et al 2000).…”
Section: Morphogenetic Responsementioning
confidence: 97%
“…While the addition of casein hydrolysate and L-proline did not affect the frequency of callus formation, they were nevertheless beneficial to embryo formation. Amino acids have been shown to exert beneficial effects on somatic embryo formation and development by providing a ready source of reduced nitrogen (Mohamed et al 2004;Bela and Shetty 1999). High levels of sucrose may exert an osmotic stress effect which is conducive to the somatic embryo induction process (Gaj 2004;Lou and Kako 1995).…”
Section: Discussionmentioning
confidence: 98%